Faktor-faktor ketidakpatuhan pembinaan menara telekomunikasi - Mohd. Ibrahim, Shuhaida (2021)
The issue of telecommunication towers construction that is often talked about is the existence of telecommunication towers without the approval of the authorities. Among the approvals involved that were ignored were Planning Permission Approval, Building Plan, Temporary Occupancy License and Special Land Permit. The towers construction without approval is not only against the rules, but can also result in enforcement and forfeiture, especially for construction on private land. This study was designed to identify the orderly procedures for the telecommunication towers construction and examine factors that influence the action of construction of telecommunication towers without approval in Kinta District. This qualitative study was designed to obtain information from the perspective of the tower builder company as a developer in the study area and involved 6 developer respondents. Data were obtained through an interview method using an interview form based on secondary data collection. Based on the descriptive analysis conducted, it was found that the level of understanding of the developer on the procedures and rules is weak, especially the understanding of the need for special permit approval. In addition, the long period of approval process also affects the actions of developers as well as non-uniform application methods between local authorities also contribute to the confusion of the correct procedure. Some research suggestions are stated to overcome the problem. In conclusion, this study is expected to help PBN improve procedures for obtaining approval for the development of telecommunication towers.